2006
DOI: 10.1086/505963
|View full text |Cite
|
Sign up to set email alerts
|

ChandraObservations of Nuclear Outflows in the Elliptical Galaxy NGC 4552 in the Virgo Cluster

Abstract: We use a 54.4 ks Chandra observation to study nuclear outflow activity in NGC 4552 (M89), an elliptical galaxy in the Virgo Cluster. Chandra images in the 0.5Y2 keV band show two ringlike features $1.7 kpc in diameter in the core of NGC 4552, as reported previously by Filho et al. We use spherically symmetric point explosion shock models to argue that the shape of the surface brightness profile across the rims of the rings and the temperature of hot gas in the rings are consistent with a Mach 1.7 shock carryin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 57 publications
(108 reference statements)
9
61
0
Order By: Relevance
“…We find that the temperature of the gas inside the discontinuity (i.e., closer to the nucleus) is marginally hotter than the gas outside the discontinuity within large errors. Given the density and (within larger errors) temperature contrast, circular symmetry, and the close association of the radio lobe with the X-ray surface brightness discontinuity, we conclude that the discontinuity is a shock in the gas created by the supersonic inflation of the radio lobe similar to features seen in NGC 4552 (Machacek et al 2006) and M87 (Forman et al 2005), among many others.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…We find that the temperature of the gas inside the discontinuity (i.e., closer to the nucleus) is marginally hotter than the gas outside the discontinuity within large errors. Given the density and (within larger errors) temperature contrast, circular symmetry, and the close association of the radio lobe with the X-ray surface brightness discontinuity, we conclude that the discontinuity is a shock in the gas created by the supersonic inflation of the radio lobe similar to features seen in NGC 4552 (Machacek et al 2006) and M87 (Forman et al 2005), among many others.…”
Section: Discussionsupporting
confidence: 51%
“…Relatively weak (Mach number, M, < 1.4) shocks have been detected in a number of systems including the Perseus (Fabian et al 2003) and Virgo clusters ), but stronger shocks where the entropy changes are largest are an apparently rare phenomenon and have only been observed in a small number of systems. Stronger shocks (M > 1.5) are most often seen in lower mass systems such as Cen A (Kraft et al 2003;Croston et al 2009), NGC 5813 (Randall et al 2011), NGC 4636 (Baldi et al 2009, and NGC 4552 (Machacek et al 2006), although shocks with similar Mach number also have been observed in the cluster gas around Her A ) and in A3847 (Croston et al 2011). Detection of additional examples of cool core clusters with active galactic nucleus (AGN) driven shocks is critical in understanding the energetics and duty cycle of such outbursts, as well as the overall thermodynamic evolution of cluster cores.…”
Section: Introductionmentioning
confidence: 99%
“…The observed X-ray properties (low L X and T ∼ T and very low L X (Figure 2, magenta symbols), though, require that f be > 0.35 for them, and then that f vary from galaxy to galaxy, or that their gas be removed by other processes such as an active galactic nucleus outburst (e.g., Machacek et al 2006;Ciotti et al 2010), a merging, or an interaction (Read & Ponman 1998;Sansom et al 2006;Brassington et al 2007). An event similar to the latter two is unlikely in the recent past for three of these ETGs (NGC1023, NGC3115, NGC3379), which are very regular in their stellar morphological and kinematic properties, but is possible in the other ETG (NGC4621) that hosts a counter-rotating core (Wernli et al 2002).…”
Section: The Temperature and Gas Flow Status In Etgs Of Intermediate mentioning
confidence: 99%
“…The size and number of cavities in the hot gas varies from one galaxy to another. As examples, NGC4636 and NGC4552 each show two primary cavities (Jones et al 2002, Baldi et al 2009, Machacek et al 2006, while M84 and the NGC5813 group show multiple cavities aligned along a single axis through the nucleus (Finoguenov et al 2008, Randall et al 2011. The cavity morphology of the group NGC5044 exhibits multiple cavities throughout its hot gas (David et al 2009).…”
Section: Overviewmentioning
confidence: 97%